THE ESSENCE OF THE ASSOCIATIVE APPROACH TO (American Journal of Pedagogical and Educational Research, 2026)
The article highlights the need to deeply study issues such as the associative connection of language units, their associative meaning, their combination into associative groups, and the organization of the associative field in the analysis of the problem of human perception of the world and its reflection in language.